Nitrogen sources and defoliation levels in cowpea bean (Research, Society and Development, 2024)
This study was aimed at evaluating the effect of artificial defoliation and different nitrogen sources on production traits of cowpea using mixed generalized linear models. The experiment was developed in a 3x5x2 factorial arrangement, being: three Nitrogen sources; five levels of artificial defoliation; and two defoliation seasons, with four repetitions. The plots were distributed in the Randomized Block Design, developed in a greenhouse and in the field. The following characteristics were evaluated: number of pods produced per plant; number of grains produced per pod; number of grains produced per plant; average length of pods; average weight of 100 grains; and estimated production. The GLIMMIX procedure was used because it allows the probability distribution of the response variable to take the appropriate distribution model. Production per Hectare (PHA) of plants subjected to leaf loss area can be increased up to 50% defoliation level, the variety Tumucumaque overcompensates in productivity, with maximum yields at 27.03% of defoliation and significant decrease above 75%, regardless of phenological stage. Even with losses above these levels, this cultivar had high indexes of productivity, revealing its high resistance to leaf loss injury. The use of chemical nitrogen fertilization and inoculation of cowpea seeds, variety Tumucumaque with Bradyrhizobium is unnecessary in the edaphoclimatic conditions of Bom Jesus – PI; The use of nitrogen fertilization with ammonium sulfate and inoculation of cowpea seeds with Bradyrhizobium does not influence the resistance of the Tumucumaque variety to defoliation levels; Defoliation levels above 75% impair the performance of production traits of cowpea, Tumucumaque.